General populations' preferences for colorectal cancer screening: rationale and protocol for the discrete choice experiment in the SIGMO study. Issue 1 (21st January 2021) - Brinkmann, Melanie; Diedrich, Leonie; Krauth, Christian; Robra, Bernt-Peter; Stahmeyer, Jona Theodor; Dreier, Maren
Abstract : Introduction: In Germany, the organised colorectal cancer (CRC) screening programme includes the immunologic faecal occult blood test and colonoscopy. The sigmoidoscopy is recommended for individuals rejecting colonoscopy but is not included into the screening programme. To examine whether the evidence based sigmoidoscopy should be additionally offered, the first objective of this study is to evaluate the demand for sigmoidoscopy by analysing the German general populations' preferences for CRC screening. Methods and analysis: Preference data will be collected using a discrete choice experiment (DCE). Identification and selection of the attributes and their levels will be supported by evidence resulting from a systematic literature search and focus groups. An efficient, fractional factorial choice design will be generated. In a cross-sectional study, the DCE will be administered as a written questionnaire to a random sample of 4000 members of the statutory health insurance company in Lower Saxony (AOK Lower Saxony). Insured persons 50–60 years of age without CRC or a chronic inflammatory bowel disease will be eligible. The collected choice data will be analysed by conducting a conditional logit regression model and latent class models. Ethics and dissemination: Ethical approval for this study was obtained from the Ethics Committee of Hannover Medical School (reference number 8671_BO_K_2019). The study results will be disseminated via conference presentations, publications in peer-reviewed journals and, to participants, the membership magazine of the AOK Lower Saxony. Trial registration number: DRKS00019010.